Perempuan Dalam Politik: Analisis Emansipasi Dari Perspektif Marxisme Dan Feminisme Dalam Pilkada Kota Kendari Tahun 2024 - Dian Trianita Lestari (CV. ITTC INDONESIA, 2025)
This research examines women’s involvement in the 2024 Regional Head Election in Kendari City, where two female candidates ran for mayor. The research problem focuses on how the concept of emancipation can be understood through feminist and Marxist perspectives in the context of local politics. The objective of this research is to analyze to what extent women’s participation in the election represents substantive political emancipation rather than symbolic representation. The research employs a qualitative method with a literature study approach. Data were collected from books, journals, and online sources, then analyzed through data reduction, presentation, and conclusion drawing. Theoretical frameworks include emancipation, feminism, and Marxism. Feminism emphasizes gender equality and substantive representation, while Marxism highlights class relations and economic-political domination in electoral processes. The findings reveal that although the presence of female candidates reflects progress in political participation, their involvement remains dominated by political elites and family dynasties. Consequently, women’s representation in Kendari’s election is more formal and symbolic than substantive. The research concludes that women’s political emancipation in Kendari still faces structural barriers of patriarchy and oligarchy. True emancipation can only be achieved if women build independent political bases, strengthen gender solidarity, and challenge class domination.